Formal complications - Schweiger, Alec, author; Bates, Haley, advisor; Harrow, Del, committee member; Moore, Emily, committee member; Malinin, Laura, committee member (Colorado State University. Libraries, 2023)
This thesis is concerned with the experiential understanding of the everyday-tactile environment. From public to private, infrastructure to daily-use objects, the things that exist in the constructed environment around me compel my investigations of material, form, and function. Specifically, how these qualities work in concert to inspire associations of purpose and value. Inhabiting a variety of formats from jewelry to sculpture to installation, the work allows me the space to pose questions about what makes an object important, and how that may be determined. The responsive decisions I make are informed by my experience with, and a sensitivity towards, materials and objects associated with packaging, adornment, domesticity, and industry.
Keywords: craft; material; ceramics; sculpture; jewelry